What defines mindfulness-based programs? The warp and the weft. Issue 6 (29th December 2016) - Crane, R. S.; Brewer, J.; Feldman, C.; Kabat-Zinn, J.; Santorelli, S.; Williams, J. M. G.; Kuyken, W.
Abstract : There has been an explosion of interest in mindfulness-based programs (MBPs) such as Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy. This is demonstrated in increased research, implementation of MBPs in healthcare, educational, criminal justice and workplace settings, and in mainstream interest. For the sustainable development of the field there is a need to articulate a definition of what an MBP is and what it is not. This paper provides a framework to define the essential characteristics of the family of MBPs originating from the parent program MBSR, and the processes which inform adaptations of MBPs for different populations or contexts. The framework addresses the essential characteristics of the program and of teacher. MBPs: are informed by theories and practices that draw from a confluence of contemplative traditions, science, and the major disciplines of medicine, psychology and education; underpinned by a model of human experience which addresses the causes of human distress and the pathways to relieving it; develop a new relationship with experience characterized by present moment focus, decentering and an approach orientation; catalyze the development of qualities such as joy, compassion, wisdom, equanimity and greater attentional, emotional and behavioral self-regulation, and engage participants in a sustained intensive training in mindfulness meditation practice, in an experiential inquiry-based learning process and in exercises to develop understanding. The paper's aim is to support clarity, which will in turn support the systematic development of MBP research, and the integrity of the field during the process of implementation in the mainstream.